Formação e Capacitação da equipe do Centro de Referência em Saúde do Trabalhador (CEREST) e sua relação com o modelo de atenção adotado: estudo de caso de Minas Gerais - Silva, Vivianne Peixoto da [UNIFESP] (2013)
The Centers for Reference in Worker’s Health (CEREST), considered as pivot axes of the actions defined by the National Network for Health Care Workers (RENAST), since 2002, act as backup technique for the SUS (National Health Service), focusing on actions of promotion, prevention and vigilance in Worker’s Health (ST) within the collective aspect. After ten years of publication of the first ordinance of RENAST, many CEREST still act in an assistencial manner, as the gateway of the network, disregarding the proposed model of attention. Studies indicate that many professionals who make up the technical teams of CEREST, relocated from the care network of public services, have not always presented education and training needs related to the activities in the field of ST (Worker’s Health). In this perspective, this research aims to analyze the relationship between the graduated professional formation and the training/ Permanent Education in ST of the crew from regional CEREST of Araxá in Minas Gerais and the actions undertaken by this, within the model of RENAST The study consisted of a qualitative study in which four methodological tools were used for data collection: 1 - semi - structured interviews with administrative and technical coordinators of the CEREST, 2 - participant observation in areas of implementation of internal and external developed actions, 3 - documentary analysis of portfolios of stock records of the years 2009 and 2010 Work Plan of the biennium: 2010-2011 and the Municipal Health Plan 2010-2013 of the City of Araxá, and 4 - a focus group with professionals in the technical team. The data collected were organized, analyzed and interpreted by content analysis (Bardin, 1988) and systematized in the following thematic categories: 1 - Composition of the technical staff as CEREST graduate training, 2 -Training in Worker’s Health, 3 - Actions taken by the team, and 4 - Points of difficulties for the development of actions.The study found that the professionals who make up the crew of the CEREST Araxá have mostly graduate training in health, without prior knowledge and / or experience in ST. Regarding the training / continuing education after entering the CEREST, it was found that the same occurs fledgling and uneven without contemplating the offer of courses for all members. As for the undertaken actions, there is a greater concentration of care guidelines for pension rights, reference and cross-reference and activities of physical therapy group, in relation to surveillance, which reflects the adopted model of care that often is at the margin of that proposed by RENAST. It could be noticed that despite the efforts of the technical team to develop actions in ST, there are many difficulties, among them are: the weakness of intra-sectorial prioritization in the absence of explicit policy of ST by the city government ; conflicts in relation CEREST-enterprises, the need for a wider multidisciplinary team, as well as ongoing training / education of the whole crew WH. Being a "bottleneck" for the implementation of actions, professional training and capacity building in ST deserve attention and reflection, without letting to consider also other difficulties encountered.